Glonate your inspiring journey with impact - Dursun, Orcun (2016)
This work project serves as the very first milestone for my own future social start-up GLONATE. The idea is to create a social giving and storytelling platform that connects donors, messengers and recipients through social interaction. The platform will enable potential donor`s to connect to messengers in order to mutually contribute to a social cause. An innovative donation chain that does not only help the needy people but also at the same time creates and shares emotional stories among all participants. The objective of this paper is to analyse the feasibility of this social giving platform and to demonstrate value proposition. Key words Social Entrepreneurship,